Keteladanan Inggit Garnasih, Sang Pemilik Simbol Kesetiaan - Trianasari, Intan; Ekawardhani, Yully Ambarsih (Fakultas Desain Universitas Komputer Indonesia, 2021)
Inggit Garnasih had a big role in Sukarno's life as a woman who had dedicated his life to helping the independence of this nation. As a gentle woman, Inggit Garnasih was able to form the character of a partner to be someone who influenced his family and nation. Basically women are able to help the formation of characters that are very influential in the survival of the nation's successors. This makes the role of women must be given more attention especially as examples of women today who need role models as role models. In his life story Inggit Garnasih teaches six sample points that are able to provide good examples, to young people who need exemplary female figures as role models. These six roles are raised as exemplary points to become models of rigidity in women's lives today. Information media in the form of romance novels become a solution to be an object of reflection and inspiration. This work is expected to encourage women to understand and emulate the role of Inggit Garnasih as an exemplary figure and to be able to apply these points in today's community life.